171k views
5 votes
X + 4y – 12 = 0 x = 3y – 7 Which of the following is the resulting equation?

-7y – 19 = 0
y – 5 = 0
7y + 19 = 0
7y – 19 = 0

User CragMonkey
by
5.5k points

1 Answer

3 votes

Answer:

The answer to your question is 7y - 19 = 0

Explanation:

Data

Equation l x + 4y - 12 = 0

Equation ll x = 3y - 7

Process

1.- Substitute equation ll in equation l

3y - 7 + 4y - 12 = 0

2.- Group like terms

(3y + 4y) + (-7 - 12) = 0

3.- Simplify like terms

7y - 19 = 0

4.- Result

7y - 19 = 0

User Evan Huang
by
5.1k points